2021
DOI: 10.1108/jima-09-2020-0261
|View full text |Cite
|
Sign up to set email alerts
|

Why do Muslims engage in adaptive worship behavior during the pandemic? The role of protection motives and religiosity

Abstract: Purpose This study aims to investigate whether the protection motivation theory (PMT) and religiosity can explain the intention of at-home worship adaptive behavior during the COVID-19 pandemic. This study further explores factors that may affect this adaptive behavior, namely, the intention to adapt behavior, religiosity, social influence and trust in the government. Design/methodology/approach Data were collected through an online survey to purposively sample the respondents, resulting in 368 responses tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 93 publications
0
5
0
Order By: Relevance
“…In the study by Alam et al (2011), religiosity has been found as an essential antecedent and significant mediator in determining the behaviour of Muslim consumers. Rostiani et al (2021) also found that religiosity drives the adaptive coping behaviour among Muslims during the Covid-19 pandemic.…”
Section: Religiosity and Sustainable Consumption Behaviourmentioning
confidence: 86%
See 2 more Smart Citations
“…In the study by Alam et al (2011), religiosity has been found as an essential antecedent and significant mediator in determining the behaviour of Muslim consumers. Rostiani et al (2021) also found that religiosity drives the adaptive coping behaviour among Muslims during the Covid-19 pandemic.…”
Section: Religiosity and Sustainable Consumption Behaviourmentioning
confidence: 86%
“…In a religion-dominant country such as Pakistan, it is pertinent to see the behavioural change expected by the Covid-19 through the lens of religiosity. Studies have investigated the impact of Covid-19 fear on religiosity (Boguszewski et al, 2020;Lucchetti et al, 2021;Rostiani et al, 2021;Wildman et al, 2020;Yıldırım et al, 2021) and SCB (Chae, 2021;Esposti et al, 2021;Jian et al, 2020) separately. However, quantitative research with primary data examining the impact of Covid-19 fear and PK on SCB with the mediating effect of religiosity is rare.…”
Section: Religiosity and Sustainable Consumption Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…The act of keeping a distance from person to person limits the probability to contact the infected surfaces of an infected person (Bzdok and Dunbar, 2020). To restrict the spread of COVID-19, all governments, including Islamic ones, adopted the preventive step of SD for mosque prayer (Rostiani et al, 2021). Organizations started following precautions for employees as well as for consumers during this difficult time.…”
Section: Covid-19 Pandemic Shoppingmentioning
confidence: 99%
“…The received social support can affect the degree of anxiety of the individual because it cannot be denied that the psychosocial changes during pregnancy affect the emotional state (Gao et al, 2020). Apart from social support, Rostiani, Toyib, & Khoiriyah (2021) explained that religiosity is one factor that affects resilience. It is believed that religious activities can promote the adaptability of individuals (including pregnant women) during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%